Dopamine modulates unitary conductance of single PL-type calcium channels in Roccus chrysops retinal horizontal cells. - Pfeiffer-Linn, C L (1996)
1. Dopamine modulation of the PL-type calcium channel of white bass retinal horizontal cells was studied in isolated, cultured neurons. Single-channel recordings were made of calcium channels in outside-out patches, under conditions which favoured the expression of calcium channel activity. 2. Analysis of single-channel properties revealed that dopamine potentiated the activity of the sustained calcium channel in three ways. First, it increased unitary conductance through individual channels. Under the influence of dopamine, single-channel conductance doubled. 3. Dopamine also increased the probability of channel opening and increased channel mean open time. The probability of opening increased 4-fold while mean open time doubled. 4. The mean closed time was also affected. The time between individual openings was not affected but the closed time between bursts of openings was shortened by over 50%. 5. The effects of dopamine were mediated via the activation of a D1-type receptor and the resulting activation of a cAMP-mediated second messenger system. 6. The combination of the effects of dopamine significantly increased the net calcium influx into the cell.